Assessing the availability of two bamboo species for fermentable sugars by alkaline hydrogen peroxide pretreatment. (April 2022) - Zhan, Yunni; Cheng, Jinyuan; Liu, Xuze; Huang, Chen; Wang, Jia; Han, Shanming; Fang, Guigan; Meng, Xianzhi; Ragauskas, Arthur J.
Highlights: AHP significantly enhanced the enzymatic saccharification of bamboo. PEB has a relatively rigid structure with stronger recalcitrance than NAB. The lignin behaviors of two bamboo samples were investigated and compared. Abstract: This study comprehensively investigated two bamboo species ( i.e. Neosinocalamus affinis and Phyllostachys edulis ) in terms of their cell wall ultrastructure, chemical compositions, enzymatic saccharification, and lignin structure before and after alkaline hydrogen peroxide pretreatment (AHP). During AHP, Neosinocalamus affinis (NAB) had higher delignification than Phyllostachys edulis (PEB), and thus showed better enzymatic digestibility (93.05% vs 53.57% for glucan). The fundamental chemical behavior of the bamboo lignins was analyzed by fluorescence microscope (FM), confocal Raman microscope (CRM), molecular weight analysis, and 2D HSQC-NMR. Results indicated that the PEB has thicker cell wall and more concentrated lignin in its compound middle lamella and cell corner middle lamella than NAB. Moreover, PEB lignin contains more G units (S/G of 0.95), in evident contrast to that of NAB lignin (S/G of 1.30), which favor the formation of C–C linkages, thus impeding its degradation during the AHP.